1999
DOI: 10.1046/j.1440-1762.1999.00337.x
|View full text |Cite
|
Sign up to set email alerts
|

A collaborative occupational therapy and nursing approach to falls prevention in hospital inpatients

Abstract: A retrospective audit of inpatient falls at the Gold Coast Hospital was conducted in August 1996. This collaborative approach of occupational therapy and nursing staff aimed to reduce the number of patients falling while they were hospital inpatients. From the first audit a number of high risk patient groups, activities and ward environments were identified and a falls prevention program implemented. A second audit conducted 2 years later demonstrated a decrease in falls and related injuries. This paper discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 13 publications
(23 reference statements)
0
50
1
Order By: Relevance
“…Once such data were excluded, the above inclusion and exclusion criteria identified 6 primary articles for review. 9,[21][22][23][24][25] Additionally, a cluster randomized fall prevention trial in a mixed inpatient population was published by Cumming et al 26 in 2008. The study was excluded, as the participants were pooled between rehabilitation wards and acute inpatient wards, and only incomplete data were reported separately for the acute inpatient wards.…”
Section: Selected Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Once such data were excluded, the above inclusion and exclusion criteria identified 6 primary articles for review. 9,[21][22][23][24][25] Additionally, a cluster randomized fall prevention trial in a mixed inpatient population was published by Cumming et al 26 in 2008. The study was excluded, as the participants were pooled between rehabilitation wards and acute inpatient wards, and only incomplete data were reported separately for the acute inpatient wards.…”
Section: Selected Studiesmentioning
confidence: 99%
“…All but 1 study had a large sample size, with 1000-patient days ranging from 11.1 to 160.3. 9,[21][22][23][24] Components of the Intervention Multidisciplinary interventions were complex, and formulated based on available evidence for individual interventions and modifiable fall risk factors (Table 3). Each study reviewed included a fall risk assessment to risk-stratify participants and modulate intervention according to risk.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…These strategies include environmental modifications (Sattin et al 1997, Smith & Widiatmoko 1998Carter, Campbell & SansonFisher et al 1997;Connell 1996), population based interventions (Beurden, Kempton, Sladden & Garner 1998;Byles, Harriss, Nair & Butler 1996;Hahn, Van Beurden, Kempton et al 1996) exercise programs (Kannus, Niemi, Palvanen & Parkkari 1997;Campbell et al 1997) and medical management of identified risks (O'Mahoney & Foote 1998;. Despite numerous attempts to identify a discrete area to target, multidisciplinary multi-factorial approaches that include preventative strategies seem to have most potential for reducing disability and death as the consequence of a falls injury (Byles et al 1996;King & Tinetti 1996;Luukinen et al 1996;Brandis 1999). This paper presents a two-year pilot falls prevention project (Fall STOP) involving the Gold Coast Division of General Practice and the Gold Coast Hospital Occupational Therapy Service.…”
Section: Introductionmentioning
confidence: 99%